Synovial changes detected by ultrasound in community-derived people with knee pain - Sarmanova, A. (2018)
Background: Knee pain, the main symptom of knee osteoarthritis (OA), affects one in 4 people aged over 55 years, of whom 10% have mild to moderate disability. The aetiology of knee pain is heterogeneous and its relationship with structural changes and function is unclear. An important role for synovial pathology in the initiation and progression of knee OA has been emphasised. However, the normal values of synovial changes detected on ultrasound (US) in the general population and their association with knee pain in community-based people with knee pain or OA remain largely unknown.